2008
DOI: 10.1007/s11610-008-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaction bone grafting procedure with distal fixation of a cemented stem with a moldered mesh: a prospective study with a 12.5-year follow-up

Abstract: A modified version of the impaction bone grafting technique was introduced in 1985. The use of a moldered metallic mesh to protect the graft from excessive cement penetration was promoted as well as to reinforce the reconstruction mechanically. The length of the revision stem was chosen to achieve distal fixation and to bridge the bone loss to prevent subsidence and postoperative femoral shaft fracture. The 8-year stem survivorship was 100% and 92.8 ± 6.8% at 12.5 years of follow-up. This technique achieved co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The influence of increased density on primary stability of impacted bone and the penetration of cement into the bone graft have to be considered. Penetration of cement was found impaired in the distal area of implanted stems since failure of specimens appeared within the impacted bone graft indicating a stable cement fixation (Coathup et al 2008 ; Frei et al 2005b ) since significant cement penetration into the bone graft could interfere with bony integration (Migaud et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of increased density on primary stability of impacted bone and the penetration of cement into the bone graft have to be considered. Penetration of cement was found impaired in the distal area of implanted stems since failure of specimens appeared within the impacted bone graft indicating a stable cement fixation (Coathup et al 2008 ; Frei et al 2005b ) since significant cement penetration into the bone graft could interfere with bony integration (Migaud et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…A mechanically stable distal fixation is important for the primary stability of the femoral implant to avoid subsidence and allow reconstruction of the bone stock (Heyligers et al 2014 ; Migaud et al 2008 ). Femoral impaction bone grafting based on the technique described by the working groups from Exeter and Nijmegen (Gie et al 1993a , 1993b ) might be indicated in case of femoral defects Paprosky 3B and 4 in particular for younger patients (Goldman and Sierra 2017 ; Heyligers et al 2014 ; Scanelli and Brown 2013 ; ten Have et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%